Posibilidades y límites de la universidad latinoamericana desde una perspectiva histórica (2011)
The Latin American University, throughout history, was shaped under the influence of diverse forces which outlined it in a particular manner, given the specific contexts where it appeared, in relation with colonial powers, the church, the State, and the impact of the different models which were established based on the purposes it had to fulfill, which were defined by the English, the French, the German, and the American people. Despite the interests which hang over the Latin American university, from diverse glances (the experiences of Mexico, Peru, Guatemala, Argentina, Chile, and Colombia) appear possibilities of considering the idea of restructuring an individual thinking which could recount a different identity that separates it from the Euro-centered discourse and places it in a perspective of analysis concerning the realities it has to deal with. In the configuration of the Latin American University, the following can stand out: Andrés Bello's thought, José Vasconcellos' ideas, and the implications of the Movement of Cordoba, as for the social and student movements with similar characteristics, which are directed toward the reflection about the need of making a decolonized change, not just as a matter of resistance, but of selfawareness of who we are and how to strengthen a common future. This is especially done in this epoch when the Latin American University is facing the attacks of globalization and the application of macroeconomic policies that blur its social and academic being, undermining it